Controlled preparation of a heterometallic lanthanide complex containing different lanthanides in symmetrical binding pockets. - Natrajan, L; Villaraza, A; Kenwright, A; Faulkner, S (2009)
A heterometallic lanthanide complex has been prepared by sequential deprotection and complexation of an orthogonally protected ligand: luminescence and NMR spectroscopy have been used to probe the integrity of the complex.